The Effect of Entrepreneurial Orientation on Marketing Performance Mediated by Absorptive Capability and Networking Capability - Reni Rupianti; Ananda Sabil Hussein; Ferry Firdaus (International Journal of Science and Society, 2022)
This research aimed to analyze the effect of entrepreneurial orientation, absorptive capability, and networking capability on marketing performance; examine the effect of entrepreneurial orientation on marketing performance mediated by absorptive capability and networking capability. The sample in this research was 140 SME owners of tempeh chips in the Sanan Industrial Center, Malang. The sampling technique in this research used purposive sampling. The data analysis technique used Partial Least Squares (PLS). The results showed that entrepreneurial orientation had a direct positive effect on marketing performance; entrepreneurial orientation had a direct positive effect on absorptive capability; entrepreneurial orientation had a direct positive effect on networking capability; absorptive capability had a direct positive relationship to marketing performance; networking capability had a direct positive impact on marketing performance; entrepreneurial orientation had a positive effect on marketing performance through absorptive capability; entrepreneurial orientation had a positive effect on marketing performance through networking capability. Absorptive capability and networking capability acted as partial mediating variables.